2001
DOI: 10.1016/s0022-5347(05)65822-3
|View full text |Cite
|
Sign up to set email alerts
|

Her-2/Neu Expression in Prostate Cancer: High Level of Expression Associated With Exposure to Hormone Therapy and Androgen Independent Disease

Abstract: High HER-2/neu expression is highly associated with exposure to hormone therapy and androgen independence. It may contribute to androgen independence in prostate cancer and identify patients with prostate cancer more likely to have disease progression, particularly those not exposed to previous hormone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 26 publications
7
58
0
3
Order By: Relevance
“…Detection of HER2 at different times might correspond to restart in the cycle of survival cells. The role of HER2 in prostate cancer progression is still debated, with divergent reports about the level of HER2 expression in HRPC Shi et al, 2001;Di Lorenzo et al, 2002;Fossa et al, 2002;Mendoza et al, 2002;Savinainen et al, 2002;Calvo et al, 2003;Hernes et al, 2004). These discrepancies could be due to the methodology used for detecting HER2, designed for detection in breast cancers, and it might be inadequate for prostate cancer tissue (Simon et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of HER2 at different times might correspond to restart in the cycle of survival cells. The role of HER2 in prostate cancer progression is still debated, with divergent reports about the level of HER2 expression in HRPC Shi et al, 2001;Di Lorenzo et al, 2002;Fossa et al, 2002;Mendoza et al, 2002;Savinainen et al, 2002;Calvo et al, 2003;Hernes et al, 2004). These discrepancies could be due to the methodology used for detecting HER2, designed for detection in breast cancers, and it might be inadequate for prostate cancer tissue (Simon et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in prostate cancer cell lines showed that an HER2/ERBB3 signalling pathway protected the AR from degradation by the ubiquitin -proteasome pathway and enhanced AR transcriptional activity at low androgen concentrations (Mellinghoff et al, 2004). Studies of clinical prostate cancer samples, however, have produced mixed data, failing to firmly establish a relationship between HER2 overexpression and progression to hormone independence (Osman et al, 2001;Shi et al, 2001;Savinainen et al, 2002;Calvo et al, 2003). HER2 gene is overexpressed in 20 -25% of invasive breast cancers and in 60% of HRPC.…”
mentioning
confidence: 99%
“…26 In an initial Phase II trial of single-agent trastuzumab therapy in patients with prostate carcinoma, no responders were observed among patients whose tumor specimens were HER-2 negative, 27 suggesting that a targeted strategy directed at HER-2-positive HRPC populations was likely to be a more optimal approach. The current study thus attempted to provide, in a larger cohort of patients with prostate carcinoma, a broader estimate of HER-2 status and to test the hypothesis that a trastuzumab-taxane combination would improve treatment outcomes in an enriched HRPC population with HER-2-positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…60 High C-ERB-B2 expression is associated with anti-androgen therapy and may contribute to androgen-independence in PC. 61 Sadasivan et al 62 found that C-ERB-B2 expression correlated with advanced stages and higher Gleason scores. Conversely Kuhn et al 63 in a preliminary study of 53 radical prostatectomy (RP) cases, found that C-ERB-B2 protein expression did not predict serological or clinical recurrence.…”
Section: The C-myc Oncogenementioning
confidence: 99%